Analisis Faktor Sosiodemografi yang Mempengaruhi Perilaku Pencegahan Transmisi Covid-19 (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Covid-19 is a new type of coronavirus that has not been previously identified in humans. Covid-19 epidemic spread far more quickly than before all over the world. Therefore, massive preventive measures are needed to reduce the spread of Covid-19. This study aimed to analyze sociodemographic factors that influence prevention behavior of Covid-19 transmission. This was a quantitative study with cross-sectional design. This study located in NTT, West Kalimantan and East Java. The time of study was in June 2020. The sample of 96 subjects were selected by stratified random sampling technique. The dependent variable is the prevention behavior of Covid-19 transmission. Independent variables are sociodemographic include age, sex, education, and employment status. The data were collected by using an online questionnaire. The data were analyzed by using multivariate analysis. The prevention behavior of Covid-19 transmission were influenced by age (b = 0.31, 95% CI = 0.02 to 0.59, p = 0.036), education (b = 2.16, 95% CI = 0.15 to 4.17, p = 0.036), and employment status (b = 2.24, 95% CI = 0.59 to 3.90, p = 0.008). Gender (b = -0.45, CI 95% = -3.64 to 2.74, p = 0.781) had no effect on the prevention behavior of Covid-19 transmission. From the results of this study, it was found that research subjects with a more mature age, high level of education, and higher employment status could take Covid-19 prevention measures well. However, in this study, the results also showed that the gender of men and women did not influence Covid-19 prevention behavior. It is interesting to study the effect of each independent variable (age, education, occupation and sex) on the dependent variable (Covid-19 transmission prevention behavior).